2014
DOI: 10.3406/revec.2014.1711
|View full text |Cite
|
Sign up to set email alerts
|

Foliar nitrogen and phosphorus resorption in an undisturbed and a Pinus pinaster Ait. planted forests in northern Turkey

Abstract: résorption foliaire de l'azote et du phosphore dans une forêt non perturbée et dans une forêt plantée de Pinus pinaster ait. dans le nord de la turquie. -La résorption foliaire est étroitement liée à la sénescence et à la conservation des nutriments et protège la plante dans sa dépendance des apports du sol. Dans la présente étude, ont été étudiées dans le nord-est de la Turquie la dynamique foliaire de l'azote (N) et du phosphore (P), l'efficacité (RE) et la profitabilité (RP) de la résorption foliaire de que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Leaf P compounds is readily resorbed, while resorption of leaf N compounds is a bit slow and PRE is of great importance with respect to nutrient use efficiency (Aerts & Chapin, 2000;Covelo et al, 2008;Salazar et al, 2011;Yilmaz et al, 2014). Our study area is severely P-limited and it has been reported that species growing in P-limiting conditions would be more favoured by high resorption efficiency and that in P-poor soils phosphorus is more limiting than nitrogen (Covelo et al, 2008;Kilic et al, 2012;Miatto et al, 2016). It has also been stated that limiting nutrients are usually more resorbed than non-limiting ones and species on infertile soils rely more on foliar resorption as compared to species on fertile soils (Yilmaz et al, 2014;Brant & Chen 2015;Miatto et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…Leaf P compounds is readily resorbed, while resorption of leaf N compounds is a bit slow and PRE is of great importance with respect to nutrient use efficiency (Aerts & Chapin, 2000;Covelo et al, 2008;Salazar et al, 2011;Yilmaz et al, 2014). Our study area is severely P-limited and it has been reported that species growing in P-limiting conditions would be more favoured by high resorption efficiency and that in P-poor soils phosphorus is more limiting than nitrogen (Covelo et al, 2008;Kilic et al, 2012;Miatto et al, 2016). It has also been stated that limiting nutrients are usually more resorbed than non-limiting ones and species on infertile soils rely more on foliar resorption as compared to species on fertile soils (Yilmaz et al, 2014;Brant & Chen 2015;Miatto et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…Reed et al (2012) stated that if NRE/PRE ratios were < 1 more P was consistently resorbed relative to N. It has been found that PRE was higher as compared to NRE in southern populations. Several authors implied that P compounds in a leaf are more readily resorbed as compared to N compounds therefore PRE is more significant with respect to nutrient use efficiency than NRE (Aerts & Chapin, 2000;Salazar et al, 2011;Yilmaz et al, 2014). However, the opposite trend was found in northern populations and NRE was higher than PRE.…”
Section: Discussionmentioning
confidence: 99%
“…Resorption can be expressed as resorption efficiency (RE) and resorption proficiency (RP) respectively. RE is defined as the percentage of a nutrient recovered from a senescing leaf (Kilic et al, 2010;Yilmaz et al, 2014). RP is known as the amount of a particular nutrient that remains in fully senesced leaves and is not subject to temporal variation in nutrient concentration in green leaves or the timing of sampling (Killingbeck, 1996(Killingbeck, , 2004.…”
Section: _________________________________________________mentioning
confidence: 99%
See 2 more Smart Citations